Four paradigms and a fifth quadrant: the r2e2 model (c) and integrated care - Everard Van Kemenade (International Journal of Integrated Care, 2019)
Van Kemenade and Hardjono (2018) discern four quality paradigms in quality management: the Empirical Paradigm, the Reference Paradigm, the Reflective Paradigm and the Emergence Paradigm (the R2E2-Model©). The use of these paradigms differs according to the context.  Together they form a concept of Total Quality Management. These paradigms can be used for other disciplines and purposes as well. One could state that professionals need to be competent in ‘epistemic fluency’. Epistemic fluency is the capacity to understand, switch between and combine different kinds of knowledge and different ways of knowing about the world (Markauskaite and Goodyear, 2017). In other words professionals need to be able to use all four paradigms of the R2E2-Model © depending on the context they are in. The Master Program of Integrated Care at Utrecht University of Applied Sciences embraced the R2E2-Model © and its four paradigms to account for the quality of the content of the program. Starting point is that the alumni should be able to switch between and combine the four paradigms. And that means that in the curriculum all four must get equal attention. This poster presents how the four paradigms can present themselves in Integrated Care abd how they are covered by the two year Master Integrated Care. Special attention is given to leadership. References: 1- Markauskaite, L and Goodyear, Peter, Epistemic Fluency and Professional Education 2017 2- Innovation, Knowledgeable Action and Actionable Knowledge, Springer, Netherlands 3- Van Kemenade and Hardjono, Twenty First Century Total Quality Management: The Emergence Paradigm, 2018. TQM Journal, https://doi.org/10.1108/TQM-04-2018-0045